(untitled) (International Seven Journal of Multidisciplinary, 2024)
The concept of comprehensive education has gained prominence as a fundamental approach to guaranteeing a complete education, going beyond the traditional focus on academic aspects. Countries such as Finland, Sweden and Canada are examples of successful implementation of this model, associated with high levels of student satisfaction and academic performance. In Brazil, despite the history of discussions about comprehensive education, its implementation faces challenges due to socio-economic inequalities and political influences. Successful implementation of comprehensive education requires financial investment, a change in mentality and approach, constant monitoring and collaboration between different stakeholders. This approach targets not only the academic aspect, but also the socio-emotional, physical and cultural development of students, preparing them for the challenges of the 21st century.